2019
DOI: 10.5688/ajpe7456
|View full text |Cite
|
Sign up to set email alerts
|

The Past, Present, and Future of Virtual Reality in Pharmacy Education

Abstract: Objective. To characterize how virtual reality (VR) has been and is being used in pharmacy education, and evaluate the projected utility of VR technology in pharmacy education in the future. Findings. Virtual reality technology has been used in pharmacy education for many years to provide engaging learning experiences. Although these learning experiences were not available in the threedimensional digital environments provided by current VR, they demonstrated improvements in learning. Recent technological advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 45 publications
1
68
0
Order By: Relevance
“…This technology is a better way of improving surgical skill and solving different complex problems. 6,7 https://doi.org/10.1016/j.cegh.2019.12.010 Received 22 November 2019; Received in revised form 9 December 2019; Accepted 19 December 2019 VR is an innovative method of training for the medical group. It can be used for a range of diseases in providing adequate medical communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology is a better way of improving surgical skill and solving different complex problems. 6,7 https://doi.org/10.1016/j.cegh.2019.12.010 Received 22 November 2019; Received in revised form 9 December 2019; Accepted 19 December 2019 VR is an innovative method of training for the medical group. It can be used for a range of diseases in providing adequate medical communication.…”
Section: Introductionmentioning
confidence: 99%
“…A surgeon can now perform simulation-based training in a controlled environment as it guides doctors and surgeon to handle a difficult situation. 7,18 In orthopaedics, it is helpful to guide and give the proper movement of fingers and arms. It is a smart way for the treatment and solution of pain.…”
Section: Introductionmentioning
confidence: 99%
“…In the health and education sectors, the growing use of immersive technologies, such as Augmented Reality (AR) and Virtual Reality (VR), have generated new opportunities to enhance the development of clinical and communication skills of students as well as the way in which they learn [ 1 , 2 ]. While VR immerses the learner in a virtual world from where they cannot see the surrounding real world, AR superimposes computer-assisted virtual objects such as pictures, videos, text or animations into the real world creating a reality for the learner that is enhanced or augmented [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus AR supplements reality rather than completely replacing it [ 4 ]. It has been suggested that using AR for learning enables students to have a more absorbing and engaging environment without the loss of real world experiences [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation